Quantification of Irgafos P-168 and Degradative Profile in Samples of a Polypropylene/Polyethylene Composite Using Microwave, Ultrasound and Soxhlet Extraction Techniques (2024)
In polypropylene/polyethylene composite (C-PP/PE) production, stabilizing additives such as Irgafos P-168 are essential as antioxidant agents. In this study, an investigation was carried out that covers different solid–liquid extraction methods (Soxhlet, ultrasound, and microwaves); various variables were evaluated, such as temperature, extraction time, the choice of solvents, and the type of C-PP/PE used, and the gas chromatography coupled to mass spectrometry (GC-MS) technique was used to quantify the presence of Irgafos P-168 in the C-PP/PE samples. The results revealed that microwave extraction was the most effective in recovering Irgafos P-168. A recovery of 96.7% was achieved when using dichloromethane as a solvent, and 92.83% was achieved when using limonene as a solvent. The ultrasound technique recovered 91.74% using dichloromethane and 89.71% using limonene. The Soxhlet extraction method showed the lowest recovery percentages of 57.39% using dichloromethane as a solvent and 55.76% with limonene, especially when the C-PP/PE was in the form of pellets. The degradation products that obtained the highest degradation percentages were Bis (di-test-butyl phenyl) phosphate and Mono (di-test-butyl phenyl) phosphate using the microwave method with dichloromethane as a solvent and PP in film. Finally, the possible mechanisms for forming the degradation compounds of Irgafos P-168 were postulated